Birth in Italy between outcomes, appropriateness and responsibility - Giuseppe Ettore; Giuseppe Murolo; Laura Ferrara; Carla Ettore (Hygeia Press di Corridori Marinella, 2014)
Maternal mortality and morbidity related to perinatal events are increasingly rare in advanced countries. Maternal death events represent an indicator of the overall health and development conditions of a country. In Italy, similarly to other industrialized countries, the maternal mortality ratio has been approximately 3 cases per 100,000 live births. However, recently, it has been measured as 11 cases per 100,000 live births, with a severe maternal morbidity rate of 2‰. The neonatal mortality rate has been, instead, constant at approximately 2.4‰ live births, with a rate of childhood cerebral palsy of 2‰. The incidence of caesarean section in Italy is 38% on average. It is the highest in Europe, with significant regional differences. The higher incidence is observed in the birth centres of South-Italy and in those with a fewer number of deliveries. The whole "birth pathway" should be organized and planned on a regional basis according to the models of organizational network of perinatal care by Hub & Spoke and according to the principles ratified by the GL (guidelines) on the Charter of Services N. 2/95, such as: equity, accountability, participation, quality and safety of care, humanization. However, an obstacle to the implementation of this program is represented by the exponential and manufactured increase of medico-legal controversies (+ 250% of complaints over the last 15 years) with over 98% of acquittal in favour of the doctors for the Supreme Court. This issue discredits the entire medical profession and is responsible for the recourse to defensive medicine which drains each year 10bn euros. Therefore, a joined action among the legislature, the professional associations and the civil society is needed.   Proceedings of the 10th International Workshop on Neonatology · Cagliari (Italy) · October 22nd-25th, 2014 · The last ten years, the next ten years in Neonatology Guest Editors: Vassilios Fanos, Michele Mussap, Gavino Faa, Apostolos Papageorgiou